DEALING WITH STRESS IN TEACHER PROFESSION: INDIVIDUAL AND ORGANIZATIONAL STRESS MANAGEMENT MEASURES - Stasiunaitiene, Egle; Kupcikiene, Ilona; Navickiene, Lijana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Teaching is considered to be one of the most stressful professions. Bad social status of teacher in society, low salary, abundance of work roles, the need to work overtime, education reforms, disrespectful behavior of learners, high demands - all these factors and many others cause teachers‘ stress in their professional activity. The study is aimed at identifying individual and organizational practices that are used to cope with teacher stress as well as finding out what are the main stress management gaps and areas which need to be improved at organization level and individually. A quantitative survey conducted in five European countries revealed that the most frequent stress management measures used at individual level relate to rational practices focused on managing thoughts and promoting rational and positive thinking. Also different organizational interventions are implemented at school level to promote teachers’ motivation, participatory environment, open communication and support. However, these measures are insufficient. They need to be strengthened and expanded in order to promote more supportive work environment and trainings targeted to fill the gaps in school staff knowledge and skills on resolving conflicts and stress different management techniques.